The Effect of Capital Structure Decisions on Profitability of Quoted Consumer Goods in Nigeria - Kalu, Awah Stanley; Thaddeus, Ebiringa Oforegbunam; Enyinna, Ugwu Kelechi (Journal of Empirical Studies, 2020)
The study examined the effect of capital structure decisions on profitability of quoted consumer good firms in Nigeria. Research method adopted is ex-post facto research design. The study employed secondary data obtained from the websites of the consumer goods sub-sectors of the manufacturing sector, published annual reports and statements of accounts of the sampled firms and the Nigerian Stock Exchange F-act-book. The study adopted judgmental sampling and multi-stage sampling techniques in data collection. Multiple Regression models were used in the analysis of the data. The estimation result also showed that the retained earnings to asset ratio (REA) had a direct relationship with return on asset of quoted consumer goods firms in Nigeria. The study concludes that, retained earnings to asset ratio positively influenced return on asset of quoted consumer goods firms in Nigeria at 5% level of significance. The study recommends firms' managers and financial advisors to advise the stakeholders of quoted consumer goods firms to use more of internal fund to finance a huge proportion of their assets if available. Again, the firms' managers are advised to continuously study the market and advice firms on the appropriateness of the proportions of long-term debt to be used during capital structure decisions to avoid the adverse effect of financial distress.